A kind of alcohol-based rheological coating and preparation method thereof
By adopting the alcoholic flow change coatings of specific composition and preparation methods, the phenomenon of coating, accumulation, and dripping phenomenon of coating of alcoholic flow variable coatings is solved, which improves the suspension and flatness of the coating, reducing the flowing level, reducing The amount of coatings exhausted, which significantly improved the surface quality of the castings.
Patent Information
- Application Number
- CN202411247677.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-06
AI Technical Summary
When applying existing alcohol-based rheological coatings, the flow marks, accumulations, and drip hanging on the coating surface are serious, which affects the surface quality of the sand core and the casting dimensional accuracy.
An alcohol-based rheological coating composed of 80~90% composite refractory aggregate mud, 1~3% modified inorganic suspending agent, 1~3% functional additives and 4~15% first alcohol solvent, and is prepared through specific The method includes adding a binder to the second alcohol solvent, stirring and mixing, adding the first blend to the composite refractory aggregate, stirring and mixing, adding a modified inorganic suspending agent and a functional additive to the first alcohol solvent, stirring and mixing, Obtain alcohol-based rheological coatings.
It improves the suspension, leveling, thixotropy and other properties of alcohol-based rheological coatings, reduces the addition of solvents and auxiliaries, reduces the gas emission of the coating, suppresses pore defects in castings, and obtains higher coating flatness and sand core surface quality.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of casting coatings, in particular to an alcohol-based rheological coating used in sand core casting production of cast steel, cast iron and nonferrous alloys and a preparation method thereof. Background Art
[0002] With the continuous innovation and development of science and casting production technology, the requirements for casting quality are getting higher and higher. When using conventional alcohol-based rheological coatings, the flow marks on the coating surface are heavy, and the accumulation and dripping phenomena are very serious, which seriously affects the surface quality of the sand core and the dimensional accuracy of the casting.
[0003] The rheological properties of coatings are the specific manifestation of the flow and deformation laws of coatings, especially the change laws of shear stress and viscosity of coatings at different shear rates. Recently, Chinese foundry workers have introduced rheological theory into the research of foundry coatings, which has theoretically guided the research and development of foundry coatings. The rheological properties of coatings are a very important and complex comprehensive index, which affects the viscosity, shear thinning, leveling, thixotropy, anti-flow, coating, coating thickness, etc. of the coating. Summary of the invention
[0004] In order to solve the problem that flow marks, accumulation and dripping phenomena are serious on the coating surface when the existing alcohol-based rheological coating is applied, the present invention provides an alcohol-based rheological coating and a preparation method thereof.
[0005] According to a first aspect of the present invention, the present invention provides an alcohol-based rheological coating, comprising:
[0006] 80~90% composite refractory aggregate mud, 1~3% modified inorganic suspending agent, 1~3% functional additive and 4~15% first alcohol solvent;
[0007] The alcohol-based rheological coating has a suspension rate of 99.2-99.6%, a penetration depth of 0.8-1.2 mm, and a gas emission of 7.8-8.2 mL / g.
[0008] Preferably, the composite refractory aggregate mud comprises composite refractory aggregate, a binder and a second alcohol solvent.
[0009] Preferably, the composite refractory aggregate includes zircon powder, mullite powder, white corundum powder or bauxite powder.
[0010] Preferably, the binder includes phenolic resin, rosin resin, polyvinyl butyral or acrylic resin.
[0011] Preferably, the modified inorganic suspending agent comprises a composite inorganic suspending agent, a suspending aid, water and a third alcohol solvent.
[0012] Preferably, the composite inorganic suspending agent comprises attapulgite, lithium bentonite, sepiolite or rectorite.
[0013] Preferably, the suspension aid comprises diatomaceous earth, kaolin or porous alumina.
[0014] Preferably, the functional additives include microcrystalline cellulose, nano silicon powder or nano titanium dioxide.
[0015] According to a second aspect of the present invention, the present invention provides a method for preparing an alcohol-based rheological coating, comprising the following steps:
[0016] Adding a binder to the second alcohol solvent and stirring and mixing to obtain a first blend;
[0017] Adding the first blend into the composite refractory aggregate and stirring and mixing to obtain a second blend;
[0018] After adding the modified inorganic suspending agent to the first alcohol solvent and stirring and mixing, the functional additive and the second blend are added, and stirring and mixing are continued to obtain the alcohol-based rheological coating.
[0019] Preferably, the preparation method of the modified inorganic suspending agent comprises the following steps:
[0020] A composite inorganic suspending agent and a suspending aid are added to water, stirred and mixed at a temperature of 35-45°C to obtain a paste, and the paste is sealed and stored at room temperature; the stored paste is dried, cut, crushed, and ground to form a crushed material; the crushed material is added to a third alcohol solvent, stirred and mixed, and then sealed and stored at room temperature to obtain a modified inorganic suspending agent.
[0021] Preferably, the drying step comprises: drying the paste at a first temperature for a first time and then raising the temperature to a second temperature for a second time, and the drying method comprises hot air drying.
[0022] Preferably, the thickness of the paste is less than or equal to 2 cm; the first temperature is 110-130° C., and the first time is 8-10 hours; the second temperature is 190-210° C., and the second time is 2-3 hours.
[0023] In order to solve the problem of alcohol-based rheological coatings occupying parking space, the present invention has the following advantages:
[0024] 1. In the present invention, by selecting a suitable alcohol-based rheological coating and a preparation method thereof, the suspension, leveling, thixotropy and other properties of the alcohol-based rheological coating can be improved.
[0025] 2. In the present invention, by selecting a treated modified inorganic suspending agent and selecting an alcohol solvent as a solvent, the addition of solvents and other auxiliary agents can be reduced, the risk of excessive solvent infiltration into the sand core during the application process, thereby reducing its strength, and further reducing the gas emission of the coating, thereby inhibiting the occurrence of porosity defects in castings.
[0026] 3. The alcohol-based rheological coating of the present invention can be applied to a variety of coating processes, has excellent leveling performance, high coating flatness, excellent suspension stability, high shelling rate after pouring, saves energy, protects the environment, and provides a more convenient method for the transformation of traditional casting production enterprises to green and environmentally friendly production. It can be widely used in the field of casting technology. DETAILED DESCRIPTION
[0027] The present disclosure will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and thus implement the present disclosure, rather than implying any limitation on the scope of the present disclosure.
[0028] In a first aspect, this embodiment discloses an alcohol-based rheological coating, comprising, by weight percentage:
[0029] 80~90% composite refractory aggregate mud, 1~3% modified inorganic suspending agent, 1~3% functional additive and 4~15% first alcohol solvent;
[0030] The alcohol-based rheological coating has a suspension rate of 99.2-99.6%, a penetration depth of 0.8-1.2 mm, and a gas emission of 7.8-8.2 mL / g.
[0031] In this embodiment, the first alcohol solvent includes but is not limited to isopropanol or ethanol. By selecting the treated modified inorganic suspending agent and the alcohol solvent as the solvent, the addition of solvents and other auxiliary agents can be reduced, the risk of excessive solvent infiltrating into the sand core during the coating process, which leads to a decrease in its strength, and the gas emission of the coating is further reduced, thereby inhibiting the occurrence of porosity defects in the casting.
[0032] Preferably, the content of the composite refractory aggregate mud is 83-88%, the content of the modified inorganic suspending agent is 1-2.2%, the content of the functional additive is 1-2%, and the content of the first alcohol solvent is 8-13%.
[0033] Preferably, the composite refractory aggregate mud comprises composite refractory aggregate, a binder and a second alcohol solvent.
[0034] In this embodiment, the second alcohol solvent includes, but is not limited to, two or more of ethylene glycol, isopropanol and glycerol.
[0035] Preferably, the content of the composite refractory aggregate is 85-92%, the content of the binder is 0.5-2%, and the content of the second alcohol solvent is 6-13%.
[0036] In this embodiment, the composite refractory aggregate accounts for more than 80% of the coating composition, which can directly improve the rheological properties of the coating.
[0037] Preferably, the composite refractory aggregate includes zircon powder, mullite powder, white corundum powder or bauxite powder.
[0038] In this embodiment, the composite refractory aggregate is selected from two or more of zircon powder, white corundum powder, mullite powder and bauxite powder, which can meet the high temperature requirements of cast steel, cast iron and non-ferrous alloys.
[0039] Preferably, the content of zircon powder is 20-60%, the content of white corundum powder is 15-72%, the content of mullite powder is 15-42%, and the content of bauxite powder is 18-27%.
[0040] Preferably, the content of zircon powder is 20-55%, the content of white corundum powder is 15-43%, the content of mullite powder is 29-42%, and the content of bauxite powder is 18-20%.
[0041] Preferably, the particle sizes of zircon powder, mullite powder, white corundum powder and bauxite powder are different. Specifically, the particle size of zircon powder is 325 mesh, the particle size of mullite powder is 100-325 mesh, the particle size of white corundum powder is 100-270 mesh, and the particle size of bauxite powder is 180-270 mesh.
[0042] In this embodiment, refractory aggregates of different particle sizes are used for grading, so that the pores filled between the particles are reduced and the whole is evenly distributed in the suspension medium, which can effectively resist the effect of gravity, reduce the loosening of the coating system caused by aggregate sedimentation, inhibit the relative movement between particles, improve the density of the coating, and ensure the homogeneity and stability of the coating.
[0043] Preferably, the binder includes phenolic resin, rosin resin, polyvinyl butyral or acrylic resin.
[0044] In this embodiment, the binder includes two or more of phenolic resin, rosin resin, polyvinyl butyral and acrylic resin. The binder of this embodiment has good film-forming performance, high strength after curing, higher solubility in the mixed alcohol solvent composed of ethylene glycol, isopropanol and glycerol, and the obtained binder solvent has better uniformity.
[0045] Preferably, the content of phenolic resin is 0.5-0.9%, the content of rosin resin is 0.3-0.8%, the content of polyvinyl butyral is 0.9-1%, and the content of acrylic resin is 0.3-0.5%.
[0046] Preferably, the content of phenolic resin is 0.7-0.9%, the content of polyvinyl butyral is 1%, and the content of acrylic resin is 0.3%.
[0047] Preferably, the modified inorganic suspending agent comprises a composite inorganic suspending agent, a suspending aid, water and a third alcohol solvent.
[0048] In this embodiment, the third alcohol solvent includes but is not limited to one or more of ethylene glycol, isopropanol and glycerol. Water is pure water.
[0049] Preferably, the content of the composite inorganic suspending agent is 70-80%, the content of the suspending aid is 2-6%, the content of water is 8-15%, and the content of the third alcohol solvent is 8-15%.
[0050] Preferably, the composite inorganic suspending agent comprises attapulgite, lithium bentonite, sepiolite or rectorite.
[0051] In this embodiment, the composite inorganic suspending agent includes two or more of attapulgite, lithium bentonite, sepiolite and rectorite. Attapulgite is a clay with a chain-layer structure, which has a unique dispersibility and a certain bonding force. The molecular structure of lithium bentonite and rectorite is lamellar, with a large hydrophilic surface area and a strong ability to swell in water. Sepiolite has a unique nanopore structure, which can shorten the diffusion path of the solvent in the suspending agent and reduce the production cycle.
[0052] Preferably, the content of attapulgite is 20-66%, the content of lithium bentonite is 25-35%, the content of sepiolite is 10-43%, and the content of rectorite is 9-21%.
[0053] Preferably, the content of lithium bentonite is 35%, the content of sepiolite is 10-36%, and the content of rectorite is 20-21%.
[0054] Preferably, the suspension aid comprises diatomaceous earth, kaolin or porous alumina.
[0055] In this embodiment, the suspension aid includes one or more of diatomaceous earth, kaolin and porous alumina. Diatomaceous earth has a unique pore structure and stable chemical properties, and has strong adsorption; kaolin particles are in the form of small curved tubes, with a large specific surface area and strong adsorption. The filling effect and internal effect of kaolin can effectively fill microscopic pores and affect the flow properties of the coating; porous alumina AAO has excellent high temperature resistance, porosity and high specific surface area, providing more possibilities for the arrangement structure of the filler.
[0056] Preferably, the content of diatomaceous earth is 1-3%, the content of kaolin is 1.5-4%, and the content of porous alumina is 1%.
[0057] Preferably, the content of kaolin is 2.5%.
[0058] Preferably, the functional additives include microcrystalline cellulose, nano silicon powder or nano titanium dioxide.
[0059] In this embodiment, microcrystalline cellulose, nano-silicon powder and nano-titanium dioxide not only have a porous structure, but also have a certain lubricity. They can not only absorb refractory aggregates and other inorganic particles to make the components of the coating uniform, but also reduce the friction between particles, thereby ensuring the flowability of the coating at high viscosity in high solid content coatings.
[0060] In a second aspect, this embodiment discloses an alcohol-based rheological coating, comprising the following steps:
[0061] Adding a binder to the second alcohol solvent and stirring and mixing to obtain a first blend;
[0062] Adding the first blend into the composite refractory aggregate and stirring and mixing to obtain a second blend;
[0063] After adding the modified inorganic suspending agent to the first alcohol solvent and stirring and mixing, the functional additive and the second blend are added, and stirring and mixing are continued to obtain the alcohol-based rheological coating.
[0064] In this embodiment, the composite refractory aggregate and the binder solvent are pre-mixed and processed, and the binder molecules contain a large number of active functional groups, which can form chemical bonds such as hydrogen bonds with the surface groups of the powder particles of the composite refractory aggregate, produce a bonding effect through the action of chemical bond forces, and the van der Waals force between molecules also increases the bonding strength. The wrapping coverage of the binder molecules on the composite refractory aggregate particles is improved, which significantly improves the utilization effect of the binder and effectively reduces the organic content in the coating.
[0065] Preferably, a composite inorganic suspending agent and a suspension aid are added to water, stirred and mixed at a temperature of 35-45° C. to obtain a paste, and the paste is sealed and stored at room temperature; the stored paste is dried, cut, crushed, and ground to form a crushed material; the crushed material is added to a third alcohol solvent, stirred and mixed, and then sealed and stored at room temperature to obtain a modified inorganic suspending agent.
[0066] In the present embodiment, the modified inorganic suspension agent formed after a series of production and processing, the inorganic suspension agent of lamellar and pin-shaped is interwoven to form a complicated grid structure, the addition of suspension aid will further expand and reinforce the grid structure, increase specific surface area, improve the number of adsorption sites, the system space hinders the increase, effectively adsorbs and fixes the refractory aggregate particles in the coating, ensures the consistency of coating rheology, suspension and storage performance. Therefore, the rheological coating prepared by the modified inorganic suspension agent in the present embodiment, using a small amount can present a significant thickening effect, cooperate with refractory aggregate characteristics, can allocate a good self-leveling effect, thixotropic alcohol-based rheological coating. When coating obtains a certain external force, viscosity is appropriately reduced, which contributes to the extension of coating in complex sand core, after removing the external force, the kinetic energy in the grid structure at the thicker part of the coating is larger than that in the thinner part of the coating, there is a certain energy difference, coating can be promoted to continue to extend, after the kinetic energy is exhausted, the coating flow stops, and the coating thickness tends to be uniform, and the coating surface is smooth.
[0067] Preferably, the drying step comprises: drying the paste at a first temperature for a first time and then raising the temperature to a second temperature for a second time, and the drying method comprises hot air drying.
[0068] Preferably, the thickness of the paste is less than or equal to 2 cm; the first temperature is 110-130° C., and the first time is 8-10 hours; the second temperature is 190-210° C., and the second time is 2-3 hours.
[0069] In this embodiment, layered and needle-shaped inorganic suspending agents are interwoven to form a complex network structure, which is dried at a suitable temperature to obtain a certain strength and remain stable during subsequent further processing, effectively adsorbing and fixing the refractory aggregate particles in the coating, further ensuring the consistency of the coating's rheology, suspension and storage performance.
[0070] Examples 1-6
[0071] 1. The preparation method of the alcohol-based rheological coating comprises the following steps:
[0072] 1) Weigh each component according to the corresponding mass requirements of the embodiment in Table 1;
[0073] 2) Pour the composite solvent into the stirring tank, add the binder, stir at a speed of 1200r / min, and stir for 40min;
[0074] 3) Pour the composite refractory aggregate into a kneader, start the machine, stir at a speed of 160 r / min, slowly pour the blend obtained in step 2) into the kneader, increase the speed to 600 r / min, and stir for 75 minutes;
[0075] 4) Pour isopropanol into the stirring tank, add modified inorganic suspending agent, stir at a speed of 1800r / min, and stir for 40min;
[0076] 5) Reduce the speed to 450r / min, add composite refractory aggregate mud and functional additives, increase the speed to 1700r / min, and stir for 30 minutes to obtain the alcohol-based rheological coating.
[0077] Table 1 Components of alcohol-based rheological coatings of Examples 1-6
[0078]
[0079] 1.1 The preparation method of the modified inorganic suspending agent comprises the following steps:
[0080] 1) Weigh each component according to the corresponding mass requirements of the modified inorganic suspending agent in the embodiment of Table 2;
[0081] 2) Set the stirring tank temperature to room temperature, add water to the stirring tank, shear stirring speed 250r / min, add composite inorganic suspending agent and suspension aid, increase the stirring speed to 1300r / min, raise the temperature to 40℃, stir for 80min, and obtain a paste. After completion, lower the temperature to room temperature and seal for storage for 24h;
[0082] 3) The paste obtained in step 2) is sealed and stored, and is spread flat in a hot air drying oven, with a thickness of less than 2 cm and a spacing of more than 10 cm between each layer, and is dried at 120°C for 9 hours, and then heated to 200°C and dried for 2.5 hours. After the drying, the paste is cooled to room temperature, cut, crushed, and ground into 280 meshes to form a crushed product;
[0083] 4) Add the third alcohol solvent into the stirring tank, put the crushed material obtained in step 3) into the stirring tank, stir at a speed of 1600 r / min, stir for 60 minutes, then take it out and put it into an ultrasonic processor, process for 15 minutes, and then seal and store at room temperature for 48 hours to obtain the modified inorganic suspension agent.
[0084] Table 2 Components of modified inorganic suspending agents of Examples 1-6
[0085]
[0086] The properties of the coatings prepared in Examples 1-6 are shown in Table 3:
[0087] Table 3 Coating properties of Examples 1-6
[0088]
[0089] Note: The suspension rate, gas evolution and coating layer wear resistance tests are carried out in accordance with JB / T 9226-2008 standard. The permeability test method is carried out in accordance with the "Foundry Manual" (Volume 4, Chapter 11, Actual Measurement Method of Permeability). The one-time shelling rate is carried out using the conventional method "direct observation method" in this field.
[0090] It can be seen from Table 3 that the coatings obtained in Examples 1-6 have a suspension rate of 99.6% at least for 48 hours, a penetration depth of 0.8-1.2 mm, a gas emission of 0.78-8.2 mL / g, a wear resistance of 0.39-0.48 g after ignition and drying, a one-time shelling rate of 95-97%, and a high wear resistance. It can be seen that the alcohol-based rheological coatings of Examples 1-6 have excellent suspension properties and rheological properties, low gas emission, and better penetration depth. A smooth and uniform coating can be obtained. The self-shelling rate after pouring is high, which improves the surface quality of the sand core, reduces the workload of the grinding operation, saves energy, and protects the environment.
[0091] Comparative Examples 1-3
[0092] 1. The preparation method of the alcohol-based rheological coating comprises the following steps:
[0093] 1) Weigh each component according to the corresponding mass requirements of the examples in Table 4;
[0094] 2) Pour the composite solvent into the stirring tank, add the binder, stir at a speed of 1200r / min, and stir for 40min;
[0095] 3) Pour isopropanol into the stirring tank, add modified inorganic suspending agent, stir at a speed of 1800r / min, and stir for 40min;
[0096] 4) Reduce the speed to 450r / min, add composite refractory aggregate and functional additives, increase the speed to 1700r / min, and stir for 30 minutes.
[0097] Table 4 Components of alcohol-based rheological coatings of Comparative Examples 1-3
[0098]
[0099] 1.1 Preparation method of modified inorganic suspending agent in comparative example:
[0100] 1) Weigh each component according to the corresponding mass requirements of the modified inorganic suspending agent in the comparative example in Table 5;
[0101] 2) Set the stirring tank temperature to room temperature, add water to the stirring tank, shear stirring speed 250r / min, add composite inorganic suspending agent and suspension aid, increase the stirring speed to 1300r / min, and stir for 80min. After completion, seal and store for 24h;
[0102] 3) Add the product obtained in step 2) into a stirring tank, and add the third alcohol solvent, stir at a speed of 1600 r / min, stir for 60 minutes, then take out and put into an ultrasonic processor, process for 15 minutes, and then seal and store at room temperature for 48 hours to obtain.
[0103] Table 5 Components of the modified inorganic suspending agent of Comparative Examples 1-3
[0104]
[0105] The coating properties obtained in Comparative Examples 1-3 are shown in Table 6:
[0106] Table 6 Coating properties of Comparative Examples 1-3
[0107]
[0108] Note: The suspension rate, gas evolution and coating layer wear resistance tests are carried out in accordance with JB / T 9226-2008 standard. The permeability test method is carried out in accordance with the "Foundry Manual" (Volume 4, Chapter 11, Actual Measurement Method of Permeability). The one-time shelling rate is carried out using the conventional method "direct observation method" in this field.
[0109] The alcohol-based rheological coatings prepared in Comparative Examples 1-3 and the alcohol-based rheological coatings prepared in Examples 1 to 6 were used under the same conditions. The performance indicators of the comparative coatings are shown in Table 6. The highest 48h suspension rate is 90%, which is lower than the lowest 48h suspension rate of 99.2% in the embodiment. The penetration depth of the coating obtained in Comparative Examples 1-3 is lower than that in the embodiment. The wear resistance of the coating obtained in Comparative Examples 1-3 after ignition is lower than that in the embodiment. Obviously, the coating performance of the embodiment is significantly higher than that of the coating in the comparative example. After the coating obtained in Comparative Examples 1-3 is applied, there is accumulation in the grooves, and the vertical surface appears thin on the top and thick on the bottom. After the coating obtained in Comparative Examples 1-3 is poured on the casting, map-type sticky sand and pore defects appear on the surface of the casting.
[0110] According to the high-temperature casting characteristics of cast steel, cast iron and non-ferrous alloys, the characteristics of sand cores and the requirements of the application method for rheological properties, the type of composite refractory aggregate in the coating can be reasonably selected and graded, and the selected composite inorganic suspending agent, binder, suspension aid and functional additive are specially treated as a core combination to ensure the performance of the coating, which not only enables the coating to obtain good suspension, leveling and thixotropy, but also effectively reduces the amount of solvent and binder added, reduces the risk of excessive solvent infiltration into the sand core during the application process and thus causing the strength of the sand core to decrease, further reduces the gas emission of the coating, and inhibits the occurrence of pore defects in castings.
[0111] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present disclosure, and in actual applications, various changes may be made thereto in form and detail without departing from the scope of the present disclosure.
Claims
1. An alcohol-based rheological coating, characterized in that: The alcohol-based rheological coating comprises, by weight percentage: 80~90% composite refractory aggregate mud, 1~3% modified inorganic suspending agent, 1~3% functional additive and 4~15% first alcohol solvent; The alcohol-based rheological coating has a suspension rate of 99.2-99.6%, a penetration depth of 0.8-1.2 mm, and a gas emission of 7.8-8.2 mL / g; The composite refractory aggregate mud comprises composite refractory aggregate, a binder and a second alcohol solvent; The composite refractory aggregate includes zircon powder, mullite powder, white corundum powder or bauxite powder; The binder includes phenolic resin, rosin resin, polyvinyl butyral or acrylic resin; The modified inorganic suspending agent comprises a composite inorganic suspending agent, a suspending aid, water and a third alcohol solvent; The composite inorganic suspending agent includes attapulgite, lithium-based bentonite, sepiolite or rectorite; The suspension aid includes diatomaceous earth, kaolin or porous alumina; The functional additives include microcrystalline cellulose, nano silicon powder or nano titanium dioxide.
2. A method for preparing an alcohol-based rheological coating is applied to an alcohol-based rheological coating as claimed in claim 1, characterized in that: The steps include: Adding a binder to the second alcohol solvent and stirring and mixing to obtain a first blend; Adding the first blend into the composite refractory aggregate and stirring and mixing to obtain a second blend; After adding the modified inorganic suspending agent to the first alcohol solvent and stirring and mixing, the functional additive and the second blend are added, and stirring and mixing are continued to obtain the alcohol-based rheological coating.
3. The method for preparing an alcohol-based rheological coating according to claim 2, characterized in that: The preparation method of the modified inorganic suspending agent comprises the following steps: Adding a composite inorganic suspending agent and a suspending aid into water, stirring and mixing at a temperature of 35-45° C. to obtain a paste, and sealing and storing the paste at room temperature; drying, cutting, crushing, and grinding the stored paste to form a pulverized product; The crushed material is added to the third alcohol solvent, stirred and mixed, and then sealed and stored at room temperature to obtain a modified inorganic suspending agent.
4. The method for preparing an alcohol-based rheological coating according to claim 3, characterized in that: The drying step includes: drying the paste at a first temperature for a first time, then raising the temperature to a second temperature and drying for a second time, and the drying method includes hot air drying.
5. The method for preparing an alcohol-based rheological coating according to claim 4, characterized in that: The thickness of the paste is less than or equal to 2 cm; the first temperature is 110-130° C., and the first time is 8-10 hours; the second temperature is 190-210° C., and the second time is 2-3 hours.
Citation Information
Patent Citations
Cast steel coating with zirconium oxide toughened mullite as refractory aggregate and preparation method thereof
CN109128013A
High-temperature resistant coating for resin sand mold casting and preparation method thereof
CN110918869A